Analisis Data Human Resources Untuk Pengambilan Keputusan: Penggunaan Analisis Data Dan Artificial Intelligence (AI) Dalam Meramalkan Tren Sumber Daya Manusia, Pengelolaan Talenta, Dan Rentensi Karyawan - Alvina Dwi Suwandita; Vania Pijasari; Adinda Eka Diani Prasetyowati; Mochammad Isa Anshori (Pusat Riset dan Inovasi Nasional, 2023)
Purpose-The main orientation of this article is to recognize the pattern of digitalization's impact on the current development of Artificial Intelligence (AI) and human resource management and how it affects the skills needed by HR professionals for decision-making through talent management and employee retention to ensure employee capabilities by aligning work at the right time based on the company's business priority goals. Methodology-This study uses a qualitative methodology that uses descriptive research. This research focuses on decisions made by leaders to improve the quality of human resources and seeks to identify areas of knowledge that have not been explored in research. Findings-Research results show that the company's strategy of using Artificial Intelligence (AI) provides many benefits, such as improving operational efficiency, developing innovative products or services, and making better business decisions based on better forecasting and analysis. Practical Implications-Through the implications of HR data analysis as decision-making in forecasting human resource trends using AI, talent management, and employee retention. This is applied to the recruitment and selection process that provides benefits such as rewards to employees who can achieve targets. Therefore, a supportive work culture by honing the talents and potential of employees to create maximum and efficient performance can have a good impact on the company.